The Positive Facet of Self-compassion Predicts Self-reported Use of and Attitudes toward Desirable Difficulties in Learning - Wagner, Laura K.; Schindler, Simon; Reinhard, Marc-André (Frontiers in Psychology, 2017)
Previous research found that introducing difficulties and challenges during learning has desirable outcomes. With the present work, we investigated the question how the use of and the attitudes toward such learning strategies (so-called desirable difficulties) are related to self-compassion, a concept that describes the tendency to be understanding and kind to oneself when confronted with negative experiences. Evidence suggests self-compassion to be linked to less fear of failing, and further to higher control beliefs and mastery goals in learning. Given that applying desirable difficulties in self-regulated learning implies increased challenges, and further, a higher likelihood to experience a feeling of failing, we expected that the use of desirable difficulties increases with levels of self-compassion. We tested this hypothesis in an online study (N = 136) in which self-compassion and the self-reported use of and attitudes toward strategies of desirable difficulties were assessed via respective questionnaires. Results of a correlation analysis yielded first evidence for our idea. Decomposing self-compassion into a positive and a negative facet showed that the positive, but not the negative, facet is positively correlated with attitudes toward and the use of desirable difficulties. Additionally, a regression analysis showed that the positive but not the negative facet predicted attitudes toward and use of desirable difficulties, when entering both facets simultaneously as predictors. Practical implications for learners are discussed.